2022
DOI: 10.2147/ccid.s372229
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin is an Effective Component of Platycodon grandiflorus in Promoting Wound Healing in Rats with Cutaneous Scald Injury

Abstract: Background Platycodon grandiflorus could significantly improve the pathological results of cutaneous scald injury, reduce the release of inflammatory factors and promote angiogenesis. This study investigated the wound healing effect of luteolin, an active component of P. grandiflorus , on induced cutaneous scald injury in Sprague-Dawley (SD) rats. Methods The protein expression levels of TNF-α and IL-6 were detected by ELISA. QR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 49 publications
0
0
0
Order By: Relevance
“…Modern pharmacological studies have revealed that the main active ingredients in Jiegeng are triterpene saponins, flavonoids, and polysaccharides, exhibiting diverse biological activities such as anti-tumor, anti-tussive, expectorant, anti-inflammatory, anti-bacterial, and anti-oxidant properties ( Lee, Yoon, Kim, & Lim, 2004 ). Jiegeng also contains fatty acids, amino acids, vitamins, and other beneficial nutrients ( Wang et al, 2022a ). Beyond its medicinal applications, Jiegeng is widely incorporated as an edible ingredient in pickles, assorted dishes, sausages, preserved fruits, and health beverages in China, Japan, and Korea.…”
Section: Introductionmentioning
confidence: 99%
“…Modern pharmacological studies have revealed that the main active ingredients in Jiegeng are triterpene saponins, flavonoids, and polysaccharides, exhibiting diverse biological activities such as anti-tumor, anti-tussive, expectorant, anti-inflammatory, anti-bacterial, and anti-oxidant properties ( Lee, Yoon, Kim, & Lim, 2004 ). Jiegeng also contains fatty acids, amino acids, vitamins, and other beneficial nutrients ( Wang et al, 2022a ). Beyond its medicinal applications, Jiegeng is widely incorporated as an edible ingredient in pickles, assorted dishes, sausages, preserved fruits, and health beverages in China, Japan, and Korea.…”
Section: Introductionmentioning
confidence: 99%